The determination of the seismic quality factor Q from VSP data acquired using distributed acoustic sensing - Dean, Tim; Correa, J. (2017)
The spectral ratio method is the most commonly used approach to estimate the Quality factor (Q) from vertical seismic profile (VSP) data. An assumption behind this method, indeed all Q-estimation methods, is that the ability of the VSP sensor to record data is not affected by depth. Distributed Acoustic Sensing (DAS) is a relatively new method for acquiring VSP data that utilises a fibre optic cable as the sensor. DAS has the advantage of being a highly efficient method to acquire densely sampled VSP data over a large depth range simultaneously but unfortunately the frequency response of DAS data varies with velocity and thus depth. In this paper we describe a methodology that can be used to correct the frequency spectra and thus successfully estimate unbiased Q values. The methodology is demonstrated using both synthetic and real data.